Analysis of Environmental Factors Affecting Manufacturing Small and Medium-Size Enterprises in Kogi State Nigeria - Yakubu, Salisu; Yalo, Momoh I; Halilu, Uba (Journal of Social Economics Research, 2019)
This study analyzed the environmental factors affecting manufacturing SMEs in Kogi State, Nigeria. The target is to investigate the effects of internal factors as they affect the profitability of manufacturing SMEs in Kogi State. The survey research design was adopted for the study; covered 171 SME owners in Kogi State. The clusters of SMEs were located and utilized for this study. Data were analyzed using descriptive statistics, principal component factor analysis, and binary logit regression. Findings show that business strategy has a significant negative relationship with the profitability of SMEs in Kogi State. Operational strength and debt leveraging significantly and positively relate to the profitability of SMEs in Kogi State. These factors play critical roles in the sustainability of the profitability of manufacturing SMEs in Kogi State. The study recommended that manufacturing SME owners should seek knowledge and skill to crafting and adopting an effective business strategy, boost their operational strength and manage their debt leveraging distinctively to sustain their profitability in the competitive business environment of Kogi State.